EFFECTS OF SOWING DEPTH ON REMOBILIZATION AND TRANSLOCATION OF SEED PHOSPHORUS RESERVES - M. Nadeem; A. Mollier; S. Pellerin ISPA; INRA; Bordeaux Sciences Agro; Villenave dOrnon; France (Journal of Animal and Plant Sciences, 2018)
Sowing depth can affect seedling establishment due to poor remobilization and translocation of seed reserves towards newly growing maize seedling sinks. A pot study was conducted to investigate the relationship between seedling phytomass and phosphorus ( P) source-sink as affected by three sowing depths. Uniform maize seeds were planted in plastic pots at 2, 5 or 8 cm sowing depths and placed in a completely randomized design. Results revealed that seed phytomass, P hydrolysis and P translocation to newly growing sinks were significantly (pd0.05) higher at shallow sowing depths compared to deeper ones. Seed P source was efficiently utilized by seedlings at 2 cm depth due to higher P loading to leaves ( 60%) and roots (3 4%). However, developed seedling sinks at deeper depths caused a significant increase in leaf P concentrations, expressing a poor utilization of P source in terms of seedling phytomass. Results suggested a good relationship of source-sink for P remobilization and translocation at shallow showing depth and sowing seeds at 2 cm depth could results in better source P utilization and healthy crop stand for sustainable agriculture. or deeper depths could result in complete failure of
Keywords: Emergence; phosphorus; phytomass; remobilization; sink; source; sowing depth; Zea mays.